Driving mechanisms of sedimentary 230Th and 231Pa variability in the Western Arctic Ocean through the last glacial cycle - Xu, Qiang; Xiao, Wenshen; Wang, Rujian; Süfke, Finn; Lippold, Jörg; Not, Christelle (Paleoceanography and paleoclimatology, 2021)
Concentration profiles of excess 230Th and 231Pa (230Thxs and 231Paxs) in Arctic Ocean sediment cores exhibit strong temporal variabilities, but the mechanisms responsible for the variabilities remain poorly understood. Here, we present new 230Thxs and 231Paxs profiles from the Mendeleev Ridge to examine downcore 230Thxs and 231Paxs distributions and their connection to environmental conditions in the Arctic. Measurable concentrations of 230Thxs(231Paxs) from the new record display an alternation of “230Thxs(231Paxs)-rich” and “230Thxs(231Paxs)-poor” sections as observed in the other cores from the Mendeleev Ridge. Sedimentary characteristics reveal that this alternation does not directly correspond to interglacial-glacial cycles. The 230Thxs and 231Paxs concentrations show an inverse relationship to their corresponding sedimentation rates, suggesting the distributions of 230Thxs and 231Paxs are affected by variable dilution with terrigenous material. However, changes in lateral transport of these isotopes may also account for the observed oscillations. Sedimentary cumulative inventories of 230Thxs show evidence for a net deficit of 230Th in the sediments during the last glacial period, possibly due to a lack of scavenging material in general.